Conscience as a Voice of Urge to Doing Good – According to Karol Wojtyła - Jędraszewski, Marek (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2015)
This article presents a conscience as a main moral power responsible for doing good. Author bases here on Karol Wojtyła’s work (his young poems and dramas as well as his teaching as John Paul II). By listening a voice of our conscience, we are capable and eager for doing good, because we are accountable to ourselves, our deep urge, that directs us toward good and could be led by the voice of the Good which shows us a proper path and encourage to leave our previous life – like in Adam Chmielewski, St Brother Albert case – and follow His commandments. It is necessary to revitalize a voice of conscious in modern world in order to maintain an urge to doing good, inherent to every human being.